Effect of Cetyltrimethylammonium Hydrogen Sulphate on Production of Citric Acid by Aspergillus Niger Ncim-2101 - Chaurasia, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
The ability of cetyltrimethylammonium hydrogen sulphate on production of citric acid by some fungal strains such as Aspergillus-niger NCIM -2101 has been assessed. The micelle; i.e. cetyltrimethylammonium hydrogen sulphate under trial has stimulatory effect on bioproduction of citric acid and enhances the yield of citric acid to an extent of 7.694% higher in comparison to control fermenter flasks, i.e., 8.825 g/100 ml in 12 days of optimum incubation period, 1.8 pH and 30°C temperature with 28% (w/v) molasses solution along with other nutritional ingredients.